Oncologic Outcomes of Kidney-sparing Surgery Versus Radical Nephroureterectomy for Upper Tract Urothelial Carcinoma: A Systematic Review by the EAU Non-muscle Invasive Bladder Cancer Guidelines Panel - Seisen, Thomas; Peyronnet, Benoit; Dominguez-Escrig, Jose Luis; Bruins, Harman M; Yuan, Cathy Yuhong; Babjuk, Marko; Böhle, Andreas; Burger, Maximilian; Compérat, Eva M; Cowan, Nigel C; Kaasinen, Eero; Palou, Joan; et al. (European urology, 2016)
CONTEXT: There is uncertainty regarding the oncologic effectiveness of kidney-sparing surgery (KSS) compared with radical nephroureterectomy (RNU) for upper tract urothelial carcinoma (UTUC). OBJECTIVE: To systematically review the current literature comparing oncologic outcomes of KSS versus RNU for UTUC. EVIDENCE ACQUISITION: A computerised bibliographic search of the Medline, Embase, and Cochrane databases was performed for all studies reporting comparative oncologic outcomes of KSS versus RNU. Approaches considered for KSS were segmental ureterectomy (SU) and ureteroscopic (URS) or percutaneous (PC) management. Using the methodology recommended by the Preferred Reporting Items for Systematic Reviews and Meta-analysis guidelines, we identified 22 nonrandomised comparative retrospective studies published between 1999 and 2015 that were eligible for inclusion in this systematic review. A narrative review and risk-of-bias (RoB) assessment were performed using cancer-specific survival (CSS) as the primary end point. EVIDENCE SYNTHESIS: Seven studies compared KSS overall (n=547) versus RNU (n=1376). Information on the comparison of SU (n=586) versus RNU (n=3692), URS (n=162) versus RNU (n=367), and PC (n=66) versus RNU (n=114) was available in 10, 5, and 2 studies, respectively. No significant difference was found between SU and RNU in terms of CSS or any other oncologic outcomes. Only patients with low-grade and noninvasive tumours experienced similar CSS after URS or PC when compared with RNU, despite an increased risk of local recurrence following endoscopic management of UTUC. The RoB assessment revealed, however, that the analyses were subject to a selection bias favouring KSS. CONCLUSIONS: Our systematic review suggests similar survival after KSS versus RNU only for low-grade and noninvasive UTUC when using URS or PC. However, selected patients with high-grade and invasive UTUC could safely benefit from SU when feasible. These results should be interpreted with caution due to the risk of selection bias. PATIENT SUMMARY: We reviewed the studies that compared kidney-sparing surgery versus radical nephroureterectomy for upper tract urothelial carcinoma. We found similar oncologic outcomes for favourable tumours when using ureteroscopic or percutaneous management, whereas indications for segmental ureterectomy could be extended to selected cases of aggressive tumours.
Keywords: nádory močovodu; Recurrence; nádory ledvin; ureteroskopie; Ureteroscopy; Urinary tract; Organ Sparing Treatments; karcinom z přechodných buněk; Kidney Neoplasms; Kidney; Ureter; Ureteral neoplasms; Nephroureterectomy; Ureteral Neoplasms; Urothelial carcinoma; lidé; Humans; ledviny; ureter; léčba šetřící orgány; nefroureterektomie; Renal pelvis; Carcinoma, Transitional Cell; Survival